Preventive health practices and the mass media in view of the COVID-19 pandemic - Ofiaeli, Ogochukwu C.; Ebenebe, Joy C.; Nnamani, Chioma P.; Ofiaeli, Ogochukwu R.; Udigwe, Ifeoma B.; Ofiaeli, Chika I.; Chigbo, Chisom G. (International Journal Of Community Medicine And Public Health, 2022)
Background: The COVID-19 pandemic is a highly infectious disease caused by a novel corona virus. Preventive strategies are vital in controlling its spread and the mass media play a central role in disseminating needed information to the public. This study was carried out to determine how mass media has impacted on the health behaviour of individuals globally in view of the COVID-19 pandemic. Methods: This was a cross-sectional study targeting individuals in all inhabited continents of the world using an online anonymous pre-tested self-administered questionnaire. Results: The data of 485 respondents were analysed. Respondents who had heard of COVID-19 were 98.4% (477) and those who knew it was a disease caused by a new corona virus were 92.4% (448); 81.9% (397) believed COVID-19 had no cure. Information on COVID-19 was from the mass media 77.5% (376); 52.8% (256) was from the internet while 23.5% (114) was from the television. All information on COVID-19 were thought to be authentic and believable 58.8% of the time (285). Respondents would always use a face mask when away from home 47.8% (232), maintain at least an arm length from others in public 32.4% (157), wash their hands with soap and water 58.6% (284) or use an alcohol based hand-sanitizer 45.2% (219). Source of information was significantly associated with knowledge on COVID-19 (p=0.002). Conclusions: Preventive practices to militate against the spread of COVID-19 are suboptimal in view of the spread and severity of this pandemic. Most information on COVID-19 were obtained from mass media. The mass media can therefore be actively and better mobilized as means of disseminating vital information on COVID-19.